IBM KAMPUNG BURASAâ SEBAGAI BASIS KELOMPOK USAHA BURASAâ DI KECAMATAN PATTALLASSANG KABUPATEN GOWA - Rabiah, Sitti; Noer, Muli Umiaty; Ramlawati, Ramlawati (Jurnal BALIRESO, 2016)
Pattallassang districts inhabited by dozens of burasa seller which is part of Gowa regency in South Sulawesi Province, Indonesia and life in economically weak. Uniquely, burasaâ seller is selling its products in the Makassar city, but it should be a distance of tens kilometers. These activities are conducted daily, after selling burasa during the day, they started to prepare the raw materials to be processed for the night. Can be described that the job lasted for 12 hours, but provide not sufficient income for them. But their efforts were likely not accompanied by a large income. Every day they only earn IDR 100.000 for all the burasaâ they sells, which reached 100 belt burasa. Their income is not net income, but they still have to set aside capital to buy raw materials for the next day. This reality that inspires the executor team to carry out community service to the burasaâ business group who lives in the Jenemadinging village. The program aims to increase the capacity of partners to be highly competitive with traditional culinary products and encourage other partners to implement effective management and efficient business. The method used for the transfer of science and technology to partners with participatory training methods by involving as many partners as possible in the activities of lectures, discussion and practice. After the series of training, partners have been able to produce burasa with higher quality in terms of the durability of products, flavors, packaging and hygiene.